MESIODISTAL CROWN SIZE ASYMMETRY BETWEEN RIGHT AND LEFT QUADRANTS IN ORTHODONTIC PATIENTS - Syed Wasif Ali Shah; Nazir Ahmed; Akbar Ali Khan; Imran Tajik (Pakistan Oral & Dental Journal, 2020)
It has been demonstrated that, dental asymmetry is present in most populations, but this is usually clinically insignificant .This asymmetry might be due to difference in the size of the teeth on right and left sides of the human mouth. Orthodontists should be vigilant to bilateral tooth size asymmetry in treatment planning stage, as this may pose some problem in occlusal settling in finishing phase of orthodontic treatment. The aim of this study was to find out any asymmetry in the mesio-distal crown dimensions in orthodontic patients. A total of 250 plaster dental casts were collected from the Department of Orthodontics, Sardar Begum Dental Hospital, Peshawar. Mesiodistal dimensions of all permanent teeth (except 3rd molars) were measured in both arches with digital Vernier caliper with accuracy of 0.01mm. Paired t test was used for comparison of right and left side tooth size differences in both upper and lower arches. Result showed that in maxillary arch statistically significant crown size asymmetry was found in central incisors, canines and 1st molar (p = .001, .000, .006 respectively). No significant differences were found in mesiodistal crown dimensions in mandibular arch. It was concluded that statistically significant dental asymmetry was present in upper central incisors, canines and 1st molars while no dental asymmetry was found in mandibular arch. However, these differences in crown sizes were not clinically significant (more than 0.25mm).
Keywords: Asymmetry; Vernier caliper; Frequency; Dental Cast